A new species of Parastenolechia Kanazawa (Lepidoptera: Gelechiidae) from Korea, with a check list of the genus - Park, Kyu-Tek; Ponomarenko, Margarita G. (Zootaxa, 2006)
Parastenolechia suriensis, sp. nov., is described and illustrated, and P. asymmetrica Kanazawa is reported from Korea for the first time. A check list of the species of the genus is given.